Globalization and nation states – Challenges and opportunities for Pakistan - Hassan Jalil Shah; Ahmad Khan (Social Sciences and Humanities Open, 2023)
The multiple dimensions of globalization include economic, political, cultural and social aspects, with economic globalization taking precedence over the others and technology as the great enabler of globalization. Globalization and nations-state systems have been considered to at tangent to each other ever since the Peace of Westphalia in 1648. The unprecedented pace of technological development has further put the concept of nation in perils. Whereas globalization has eroded the writ of the nation-states to an extent, the Covid-19 proved to be a breather to the nations to control movement of personnel, flow of product and goods across their borders. Pakistan, located at geographically consequential location got its independence from British Raj on the basis of Two Nations Theory. However, even after 75 years of its independence, it continues to face stiff regional, economic and political challenges. State securitization vis-à-vis emasculated economy, burgeoning youth and projects like CPEC are viewed with criticality. The era of globalization renders an opportunity to analyze how some other states with identical challenges steered a path that assisted them in surmounting these challenges. In context of globalization, we shall interpret valuable lessons for Pakistan that can help the nation in crafting a way forward to overcome these dauting challenges. Applying the critical theory of globalization, this study reviews the concept of globalization and its impact on nation-states. Meanwhile, a discourse analysis has been adopted to enumerate the challenges that Pakistan faces in an economically interdependent globalized world. This is followed by case studies of various countries including India, South Korea, Bangladesh and Vietnam to understand how these nations emerged unscathed from the challenges that they withstood.